Innovation and export : the joint challenge of a small company - Enjolras, Manon (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2021)
The concepts of innovation and export are traditionally considered in isolation, both within companies and within the support organizations dedicated to them. As a result, within this broad research field, very little academic work has focused on how to implement their relationship at an operational level. This book proposes a joint diagnostic tool for SMEs, highlighting good practices to be mastered in order to simultaneously improve innovation and export performance, in the form of a virtuous circle. Innovation and Export focuses on the integration of innovation and export into the strategic management of SMEs, for which the use of synergies is a powerful lever to overcome any difficulties in mobilizing significant resources.
Front Matter -- The Relationship between Innovation and Export in SMEs. The Innovation-Export Relationship: A Complex Vision -- Joint Innovation-Export Best Practices -- PE2I, or How to Model Synergies. Design of a Joint Diagnosis Dedicated to SMEs: The PE2I -- Implementation of the PE2I: Test with French SMEs -- Feedback on the PE2I Tool -- Conclusion -- References -- Index -- Other titles from iSTE in Innovation, Entrepreneurship and Management
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Small business; Small business -- Technological innovations; Exports; Petites et moyennes entreprises -- Innovations; Exportations; Exports; Small business; Small business -- Technological innovations